The Creative Procces of Writing a Film Series “Aku Pemuda” - Budi Dwi Arifianto; Erny Kurnia Damayanti (Jogjakarta Communication Conference (JCC), 2023)
This study aims to find out how the creative process of writing scripts for the film series